Suggested languages for you:

Americas

Europe

Q31E

Expert-verifiedFound in: Page 216

Book edition
2nd

Author(s)
James Stewart

Pages
830 pages

ISBN
9781133112280

**Let \(f(x) = \frac{1}{x}\) and **

** **

**\(g(x) = \left\{ {\begin{aligned}{*{20}{l}}{\frac{1}{x}}&{ if x > 0}\\{1 + \frac{1}{x}}&{ if x > 0}\end{aligned}} \right.\)**

** **

**Show that \({f^\prime }(x) = {g^\prime }(x)\) for all \(x\) in their domains. Can we conclude from Corollary 7 that \(f - g\) is constant?**

The \(f - g\) is not constant over the whole domain. It contradicts corollary that \(f - g\) is constant although the derivatives are equal.

The functions \(f(x) = \frac{1}{x}\) and \(g(x) = \left\{ {\begin{aligned}{*{20}{l}}{\frac{1}{x}}&{{\rm{ if }}x > 0}\\{1 + \frac{1}{x}}&{{\rm{ if }}x > 0}\end{aligned}} \right.\)

**"If **\({f^\prime }(x) = {g^\prime }(x)\)** for all **\(x\)** in an interval **\((a,\;b)\)**, then **\(f - g\)** is constant on **\((a,\;b)\)**, that is **\(f(x) = g(x) + c\)** where **\(c\)** is constant".**

Obtain the derivative of \(f(x)\) as follows:

\(\begin{aligned}{c}{f^\prime }(x) &= \frac{d}{{dx}}\left( {\frac{1}{x}} \right)\\ &= \frac{{ - 1}}{{{x^2}}}\end{aligned}\)

Obtain the derivative of \(g(x)\) for \(x > 0\) as follows:

\(\begin{aligned}{c}{g^\prime }(x) &= \frac{d}{{dx}}\left( {\frac{1}{x}} \right)\\ &= \frac{{ - 1}}{{{x^2}}}\end{aligned}\)

Obtain the derivative of \(g(x)\) for \(x < 0\) as follows:

\(\begin{aligned}{c}{g^\prime }(x) &= \frac{d}{{dx}}\left( {1 + \frac{1}{x}} \right)\\ &= 0 + \left( {\frac{{ - 1}}{{{x^2}}}} \right)\\ &= \frac{{ - 1}}{{{x^2}}}\end{aligned}\)

For the case \(x > 0\), from the above equations, \({f^\prime }(x) = {g^\prime }(x)\) and for the case \(x < 0\), from the above equations, \({f^\prime }(x) = {g^\prime }(x)\).

Hence, the statement is showed for all \(x\) in their domains.

Subtract the given functions as follows:

For the case of \(x > 0,f - g\) will be as follows:

\(\begin{aligned}{c}f(x) - g(x) &= \frac{1}{x} - \frac{1}{x}\\ &= 0\end{aligned}\)

For the case of \(x < 0,f - g\) will be as follows:

\(\begin{aligned}{c}f(x) - g(x) &= \frac{1}{x} - \left( {1 + \frac{1}{x}} \right)\\ &= \frac{1}{x} - 1 - \frac{1}{x}\\ &= - 1\end{aligned}\)

Hence, it can be concluded that \(f - g\) is not constant over the whole domain. It contradicts corollary that \(f - g\) is constant although the derivatives are equal.

94% of StudySmarter users get better grades.

Sign up for free